'Global' Saving and Interest Rate Behaviour: Why Don't International Capital Markets Clear? - FitzGerald, E (1996)
This paper examines the empirical evidence on saving trends in the global economy and the emergence of a single real long-term interest rate, from a Keynesian point of view. The essentially Ricardian position of bodies such as the IMF implies a 'savings shortage' which is theoretically implausible, and non-clearing market may be better explained by Keynesian concepts of liquidity applied to asset preference. The empirical evidence seems to indicate that global capital markets do not act so as to integrate national saving pools, despite interest rate convergence among both industrialized and industrializing countries. The resulting 'rationed market' reflects uncertainty among investors as to future macroeconomic conditions, which in turn results from the failure of major economies to coordinate government fiscal stances.